Rizaldy - Evasco, Eugene Y. (Chikiting Books, 2011)
"An ordinary boy discovers heroism and greatness as he goes through a simple journey to know where his name came from. The simplicity is captured in charmimg but well-researched visuals that give the young reader a pleasant introduction to Jose Rizal.